A critical appraisal of system-reported Organ Dose (OD) versus manually calculated Mean Glandular Dose (MGD) in Dubai’s mammography services - Mohammad Noor, Kaltham Abdulwahid; Mohd Norsuddin, Norhashimah; Abdul Karim, Muhammad Khalis; Che Isa, Iza Nurzawani; Ulaganathan, Vaidehi (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: This study compares system-reported organ doses (ODs) to manually calculated mean glandular doses (MGDs) in mammography across multiple centers and manufacturers in Dubai. Methods: A retrospective study of 2754 anonymized mammograms from six clinics in Dubai were randomly retrieved from a central dose survey database. Organ doses were documented along with other dosimetry information like kVp, mAs, filter, target, compression force, and breast thickness. Mean glandular doses, MGDs, were calculated manually for all the patients using the Dance formula and inferential statistical analyses were run to compare the two figures and verify the factors affecting each. Results: Our study’s analysis revealed that manually calculated mean glandular doses (MGDs) provide a more reliable indicator of radiation exposure than organ doses (ODs) reported by DICOM, particularly in multi-vendor scenarios. Manually calculated MGD values were consistently lower than system-reported ODs (MLO view: 0.96 ± 0.37 mGy vs. 1.38 ± 0.45 mGy; CC view: 0.81 ± 0.33 mGy vs. 1.22 ± 0.38 mGy). Significant differences in both system-reported ODs and manually calculated MGDs were observed across centers (p < 0.001). Strong correlations between system-reported ODs and manually calculated MGDs were found for Siemens equipment (r = 0.923, p < 0.001) but only moderate correlations for GE systems (r = 0.638, p < 0.001). Calculated MGD values were significantly higher for GE equipment compared to Siemens (1.49 ± 0.77 mGy vs. 0.93 ± 0.33 mGy, p < 0.001). Conclusions: This study addresses concerns regarding mammography dosimetry accuracy by demonstrating the superiority of mean glandular doses over DICOM-generated organ doses. These findings empower practitioners to optimize dose levels, ensuring safer and more effective breast cancer screening protocols.